2023
DOI: 10.3389/fnagi.2023.1223015
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and prognosis in acute ischemic stroke: a dose–response meta-analysis of cohort studies

Wenyuan Zhang,
Zicheng Cheng,
Fangwang Fu
et al.

Abstract: BackgroundThere have been contradictory findings regarding the relationship between serum uric acid levels and prognosis in acute ischemic stroke. Whether this association is nonlinear due to uric acid’s paradoxical properties (antioxidant and prooxidant) is unclear.MethodsWe searched PubMed, Web of Science, and Embase databases until December 2022. Cohort studies reporting serum uric acid levels and functional outcome, mortality, or neurological complications in patients with acute ischemic stroke were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Excluding the outlier studies and then conducting the forest plot analysis again showed that there was no heterogeneity in the remaining six studies. (I 2 = 45.8%, P = 0.100) ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Excluding the outlier studies and then conducting the forest plot analysis again showed that there was no heterogeneity in the remaining six studies. (I 2 = 45.8%, P = 0.100) ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 90%
“…2 ). However, the high degree of heterogeneity (I 2 = 89.0%, P < 0.001) was observed; thus, the random-effects model was used to pooled SMDs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations